MENURUNKAN REJECT OVERLAP INNERSEASONING OIL MIE GORENG DENGAN METODE FAULT TREE ANALYSIS (FTA) DAN FAILURE MODE AND EFFECT ANALYSIS (FMEA) DI PT. TRIMITRA INDOPLAST MANDIRI - Kurnia, Ismail (Universitas Krisnadwipayana, 2023)
PT. Trimitra Indoplast Mandiri is a flexible packaging manufacturing company that provides packaging printing services based on LDPE, LLDPE, PET and Nylon. PT Trimitra Indoplast Mandiri, especially in the dry and printing line, the quality control section has problems where there are still a variety of dry & printed products that do not comply with quality standards such as types of defects, number of defects, and causative factors. Therefore, it is necessary to overcome these defective products. Quality improvement was carried out in this study using the fault tree analysis and failure mode and effect analysis methods to determine the root causes of product defects which would later reduce the defect rate according to the target defects in the dry & printing line by 2%. From the results of the data calculation, it was found that the inner seasoning oil for fried noodles had a total defect of 2449 pcs. Based on the pareto diagram that has been made of 4 types of product defects, the largest type of defect is found in overlapping defects with a proportion of 70% with a total of 1709 pieces of product. Based on the fault tree analysis, the most influential causal factor is the method factor. Furthermore, the failure mode analysis and the effect of the largest RPN values are 320 and 245, namely the material will shift far away not according to the design and produce wrong printing results. And after making improvements in the form of pokayoke design on the bearing guide roll and as shaft unwinder, it turned out that it was able to reduce the reject results in the products produced. As well as succeeding in reducing the reject rate of inner seasoning oil for fried noodles according to company standards by 2%, from which initially there was a proportion of rejects obtained by 5% to 1.96%.